Preventing Escape of Non-Native Species from Aquaculture Facilities in Florida, Part 2: Facility Evaluation Strategies - Jeffrey E. Hill; Quenton M. Tuckett; Carlos V. Martinez; Jared L. Ritch; Katelyn M. Larson (EDIS)
Understanding how non-native species escape or are accidentally released helps producers better design and operate aquaculture facilities to reduce or prevent escape. Active management of critical points where escape is possible will help achieve regulatory compliance. This 6-page fact sheet is the second in a four-part series devoted to educating industry and other stakeholders on the importance of preventing the escape of non-native species from aquaculture facilities, as well as strategies for non-native species containment and regulatory compliance. It describes farm layouts, explains how fish escape, and outlines a process that aquaculturists can complete to identify potential escape points on their farms. Written by Jeffrey E. Hill, Quenton M. Tuckett, Carlos V. Martinez, Jared L. Ritch, and Katelyn M. Lawson, and published by the School of Forest Resources and Conservation Program in Fisheries and Aquatic Sciences, August 2016.